Persian and Hellenistic Jaffa: Re-Examining Jacob Kaplan's Excavations in Area A (1970-1974) - Danielson, Andrew J. (Ancient Near Eastern studies, 2020)
A contextual examination of the unpublished excavations from Area A in Jaffa, Israel has yielded important new insights into the phases of occupation at the site dating to the Persian and Hellenistic periods. The analysis of the stratigraphic sequence from the excavation records of Jacob Kaplan (1970-1974), combined with targeted new excavations and analysis by the Jaffa Cultural Heritage Project (2014-2016) have revised the preliminary interpretations of Jacob Kaplan and yielded new insights into the Persian and Hellenistic-period phases of Area A at Jaffa. As such, four distinct phases can be elucidated, revealing patterns of domestic, economic and industrial activities within the area.